(untitled) - Ewing, A. F. (Paris, 1970)
Over the past forty years, industry has moved from the developed to the developing world, yet Africa’s share of global manufacturing has fallen from about 3 percent in 1970 to less than 2 percent in 2014. Industry is important to low-income countries.
Keywords: Công nghiệp,Industries; Châu Phi,Africa